Elevation of intracellular Na(+) induced by hyperpolarization at the dendrites of pyramidal neurones of mouse hippocampus - Tsubokawa, Hiroshi (Blackwell Science Inc, 1999)
1. Whole-cell recordings were made from CA1 pyramidal cells in mouse hippocampal slices with patch pipettes containing the sodium indicator dye SBFI (sodium binding benzofuran isophthalate). Using a high-speed imaging system, we investigated changes in intracellular sodium concentration, [Na(+)](i), in response to hyperpolarizing pulses applied to the soma. 2. In current-clamp recordings, we detected increases in [Na(+)](i) during negative current injection. Hyperpolarization-induced [Na(+)](i) elevation was more prominent in the middle apical dendrites than in the soma. 3. In the voltage-clamp mode, hyperpolarization induced rapid increases in [Na(+)](i) at the apical dendrites that were significantly faster than those at the soma. The signals were not affected by bath application of 1 μM TTX, but were reduced by 5 mM CsCl. 4. Changes in membrane potential recorded from the apical dendrites in response to negative currents were significantly smaller than those recorded from the soma. In the presence of 5 mM CsCl, the I-V relationships measured at the soma and the dendrites became almost identical, indicating that CsCl-sensitive components are predominantly in the apical dendrites. 5. These results suggest that hyperpolarization-induced [Na(+)](i) elevations reflect Na(+) influx through the non-selective cation channel (I(h) channel), and that this channel is distributed predominantly in the apical dendrites. The non-uniform Na(+) influx may contribute to integrative functions of the dendrites.